Kingdom of Nauvoo: the rise and fall of a religious empire on the American frontier - Park, Benjamin E. (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2020)
Soil -- Seeds -- Roots -- Trunk -- Branches -- Fruit -- Harvest -- Legacies.